New record and range extension of the big‐scale sand smelt Atherina boyeri Risso, 1810 (Atherinidae) in the Devegecidi Dam Lake, Tigris River basin, Turkey. (14th September 2016) - Ünlü, E.; Gaygusuz, Ö.; Çiçek, T.; Bilici, S.; Coad, B. W.
Summary: The big‐scale sand smelt, Atherina boyeri, is recorded from the Devegecidi Dam Lake in 2016, the first record of this invasive species in the Tigris River basin, with potential to extend to all countries in the Middle East. The smelts were caught with a trawl net mesh size of 6 mm. The captured specimens are described and compared. Records of A. boyeri from Turkish inland waters are summarised from the literature.